The Influence Of Service Quality And Consumer Trust On Interestrepeat Purchases With Customer Satisfaction As An Intervening Variable (Survey On Consumers Of Msme Products In West Kuningan) - Wely Hadi Gunawan.; Najmudin Najmudin; Sudarto Sudarto (Cita konsultindo, 2024)
The aim of this research is to analyze the influence of service quality and consumer trust on repurchaseintention with customer satisfaction as an intervening variable (study of Shopee Mall MaybellineIndonesia consumers in Kuningan, West Java). The population of this research is MSME users who havepurchased MSME products in Taman Kota Kuningan Regency. The sampling technique used was theHair formula. So, through calculations based on the Hair formula, the sample size obtained from this research was 150 people from the Kuningan Regency community in the MSMEs of Kuningan Regency.The results of the questionnaire obtained were 150 respondents consisting of 17 male respondentsand 133 female respondents. The data processing and analysis process uses SEM (Structural EquationModeling). The results of this research show that 1) Service Quality has a positive and significant effect on Customer Satisfaction, 2) Consumer Trust has a positive and significant effect on CustomerSatisfaction, 3) Service Quality has a positive and significant effect on Repurchase Intention, 4)Customer Satisfaction has a positive and significant effect on Repurchase Intention, 5) Consumer Trusthas no significant effect on Repurchase Intention.